Incentive mechanism-based influential maximisation scheme for social cloud service networks. (28th January 2020) - Kim, Sungwook
The integration of social network services (SNS) and cloud computing (CC) is a technological revolution that presents the future of connectivity and reachability. This paper explores the novel paradigm for future internet of things (IoT). Although there have been some studies in social-driven IoT, they merely consider the CC technique to improve service qualities and influences. In this study, we develop a novel social cloud control scheme based on the incentive mechanism (IM) approach. To maximise the total SNS system performance, SNSs have been adaptively executed in the CC system while taking into account the social welfare. In addition, we protect each user's privacy according to the differential privacy (DP) method. Therefore, our study can capture the properties of SNS and CC, and provides an effective solution for the social cloud system while ensuring privacy. The experimental results demonstrate the efficiency and effectiveness of the proposed scheme.